Effect Of Fluoride And Acid On Shape Memory Behaviours Of Niti Orthodontic Archwire - Yahaya, Muhammad Azizi (Universiti Sains Malaysia, 2017)
Nickel-Titanium (NiTi) Shape Memory Alloy (SMA) is new material that had been widely used in orthodontic application that replacing stainless steel. It is refer to larger elastic strain relieved by martensitic phase transformation. However, these wire properties will influence by the surface erosion of the wire and lead to Nickel release that may toxic to human. The surface erosion of the wire normally occur in oral environment due to eating behaviour or tooth brushing activity that will reduce the thermal and mechanical behaviour of wire. In this research, sodium fluoride and lactic acid was used to study its effect toward thermal and mechanical behaviour of NiTi arch wire. It was found that the longer the exposure time in acidic solution, the thermal and mechanical properties will reduce more compare to fluoride solution. This is proven by surface morphology on the SEM image, that obviously show that the erosion on the surface of orthodontic wire will reducing the thermal and mechanical behaviour and also lead to Nickel ion release into the human body. It can be concluded that higher value of acidity contribute high rate of corrosion toward the orthodontic arch